Upacara Daur Hidup dalam Pernikahan Adat Sunda - Mu'min Maulana (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2013)
Custom of wedding ceremony in Sunda ethnic has three parts: before wedding (pre-luminal), wedding procession (luminal) and after wedding (postluminal).This wedding of Sunda custom directly or indirectly has symbols and meanings which have absorbed Islamic values, which came in the fifteenth century in the Sunda Land. Hence, Sunda values and norms have completed Islamization. This Islamizaion is still going, without eliminating those values and customs which do not contravene Islamic religion.DOI: 10.15408/ref.v13i5.916